Voyage de la Propontide et du Pont-Euxin - Le Chevalier, Jean-Baptiste, 1752-1836. (Paris)
2 cilt (1. c. [1] katlı harita, xii, 168 sayfa, [2] katlı harita ; 2. c. [1] katlı harita, sayfa [169]-416, [1] katlı harita)